RESILIENSI: MENJAGA KETAHANAN MENTAL DALAM MENGHADAPI TANTANGAN HIDUP - Faridah, Faridah; K, Sulfikar; Mansur, Ahmad Yasser; Al Anshori, M. Zakaria (Universitas Islam Ahmad Dahlan, 2025)
Mental resilience is the ability of individuals to remain stable and thrive in the face of stress, challenges, and life changes. This study examines the importance of resilience in maintaining mental health when facing various life challenges. By utilizing psychological and sociological approaches, the purpose of this study explores strategies and factors that influence resilience, as well as their implications for improving quality of life. This study uses a literature study method. The results of this study highlight the importance of resilience development as an integral part of prevention and intervention efforts in mental health. The practical implications of this study can help individuals and communities face life challenges more effectively and productively. These findings provide important insights for individuals, communities, and institutions in efforts to support mental resilience and create an environment conducive to psychological growth.